ACTIVITY OF ALANIN AMINOTRANSFERASE AND ASPARTAT AMINOTRANSFERASE IN BROILER WITH ADDITION OF TEMULAWAK FLOUR IN FEED - Puspa Adhi, Putu Diah; Ardana, Ida Bagus Komang; Kendran, Anak Agung Sagung (Buletin Veteriner Udayana, 2020)
Curcuma ( Curcuma xanthorrhiza Roxb .) is one of the medicinal plants, which is widely used by the community, including used a lot in animals because it has many benefits for health. The purpose of this study is to find out the effect of the addition of curcuma flour on the feed toward the activity of ALT and AST on the broiler. This study used a Completely Randomized Design (CRD) with 24 female broilers aged 14 days which were divided into four groups, namely group P0 (normal feed without addition of curcuma flour), P1 group (curcuma flour 10gr/kg of the feed)), P2 (curcuma flour 20gr/kg of the feed)), and P3 (curcuma flour 30gr/kg of the feed)). After 35 days, the blood is taken through the brachial vein using 5ml syringe. Then, the examination of ALT and AST activity is conducted by using Photometer 5010. The data were analyzed by using ANOVA. The results showed that the addition of curcuma flour in broiler's feed did not affect the activity of ALT and AST (P>0.05). From the study, it can be concluded that the addition of curcuma flour in broiler's feed the dose 10 gr/kg of feed until 30 gr/kg of feed for 21 days were still classified as safe dosage.